DISCUSSION ISSUES OF TERMINATION OF EMPLOYMENT LEGAL RELATIONS BY AGREEMENT OF THE PARTIES - Зеленський, В. М. (Київський національний університет імені Тараса Шевченка, 2020)
The article focuses on outlining and the author's vision of solving some of the problematic issues of terminating labor relations by the parties’ mutual consent. The work raises the issues as follows: the submission of an application for terminating the labour relationship by the parties’ mutual consent; filing the application pointed (and the corresponding termination of labor relations) during the period of temporary incapacity for work and during vacation; withdrawal of the application.

Стаття присвячена окресленню та авторському баченню вирішення деяких проблемних питань припинення трудових правовідносин за угодою сторін. Підіймаються такі питання як: подача заяви про припинення трудових відносин за угодою сторін; подача вказаної заяви (та відповідне припинення трудових правовідносин) під час тимчасової непрацездатності та під час відпустки; відкликання заяви.
ДИСКУСІЙНІ ПИТАННЯ ПРИПИНЕННЯ ТРУДОВИХ ПРАВОВІДНОСИН ЗА УГОДОЮ СТОРІН
Keywords: Key words: termination of labour legal relationship; the parties’ mutual consent; application; vacation; temporary incapacity; withdrawal of the application; Ключові слова: припинення трудових правовідносин; угода сторін; заява; відпустка; тимчасова непрацездатність; відкликання заяви